Why Millennials Job Hop: Navigating Pay, Culture, and Growth - Ami Fitri Utami; Ghita Ihwanul Shalihah; Trihadi Pudiawan Erhan (Bina Nusantara University, 2025)
The phenomenon of job hopping, predominantly observed among millennials, has been a subject of interest. The research aimed to determine what factors influence job-hopping behavior, which was widespread among millennials, and how they influenced it. Three antecedents were analyzed, including organizational culture, perceived compensation conditions, and the availability of career development opportunities. The research used a quantitative method, where a questionnaire was used to gather data. There were 329 millennial respondents gathered, and Partial Least Squares-Structural Equation Modeling (PLS-SEM) was used to analyze the data. The results show that compensation has a positive influence, while work culture and career development negatively influence job-hopping behavior. It suggests that while higher compensation increases job-hopping, improving work culture and career development can decrease it. In this case, compensation is no longer the main factor for millennial employees to stay in their jobs or current organizations. The result also concludes that organizations should provide more consideration in developing an aligned culture with millennials’ values and creating a more transparent, structured, and accessible career development plan. The research contributes to the body of knowledge on millennials’ job-hacking behavior research by integrating the organizational practices factor towards individual behavior, particularly the millennial workforce. The research differs from previous research, which usually focuses on individual factors such as job satisfaction and exhaustion. The research has several limitations, including the number of respondents and geographical coverage. Hence, a larger sample and expanded geographical survey coverage are needed to enhance the potentiality of generalization of the research result.